Stimulation of bone regeneration with pigment epithelium-derived factor microparticles: Evidence in silico, in vitro and in vivo - Lee, P.; Martinez, Jorge; Dass, Crispin (Govi Verlag Pharmazeutischer Verlag GmbH, 2016)
The occurrence of bone defects can be due to a variety of factors not limited to bone fractures and tumours. Most diseased bone is removed and the patient fitted with prosthetics, prior to use of certain factors such as bone morphogenetic proteins (BMPs) to aid healing. Recently, the protein pigment epithelium-derived factor (PEDF) and the polysaccharide chitosan have been found to have promising effects on the regeneration of bone, with the major advantage of these agents being their safety to date. A study was performed to determine whether the combination of both chitosan and PEDF would enhance greater bone regeneration effects. Post-formulation, in silico tests (particle sizing and surface charge determination) were followed by several cell-based assays (microparticle cellular uptake, cytotoxicity, mitochondrial abundance, bone mineral formation, colony formation in matrigel, and colony formation in collagen I matrix), and finally in vivo testing where microparticles were injected periosteally in the hindlimb. Collectively these findings support the idea that PEDF microencapsulated within chitosan promotes bone regeneration, and has potential for bone trauma management. Future studies will examine the ability of this promising bone regeneration microparticle to heal bone in disease states such as fracture and tumour-mediated osteolysis.